PENGARUH PENERAPAN PEMELIHARAAN GARDU DISTRIBUSI 20KV MENGGUNAKAN METODE MINIM PADAM PADA NILAI SAIDI DAN ENS DI PT. PLN (PERSERO) AREA BULUNGAN (KB 11B) - Arif Fadhillah Fajri; Nurwijayanti Kusumaningrum (JURNAL TEKNOLOGI INDUSTRI, 2022)
Maintenance is carried out by turning off the distribution substations, causing the electricity supply to the customers to go out during the maintenance. This is a concern because customers feel an outage that will impact SAIDI (System Average Interuption Duration Index) and ENS (Energy Not Supply). This research will discuss the maintenance of the distribution substation of 20 KV PT. PLN (Persero) Bulungan Area with a minimal outage method in order to reduce the SAIDI (System Average Interruption Duration Index) and ENS (Energy Not Supply) values for maintenance. Maintenance of 20 KV distribution substations with minimal outage method, duration of outage decreased by 74.13%, SAIDI (System Average Interuption Duration Index) maintenance decreased from 0.0067 hours / customer to 0.0017 hours / customer, ENS (Energy Not Supply) decreased from 1,875,426 KWH to 485.1 KWH and Energy Not Sold decreased from Rp 2,751,775.06 to Rp 711,777.53. Maintenance of the 20 KV distribution substation using the minimal outage method greatly affects the reliability of the distribution of electric power in the low voltage network and decreases the duration of the blackout by 74.13%.Keywords: Distribution substation, Bulungan Area, SAIDI, ENS.